Pengabdian Kepada Masyarakat melalui Kegiatan Pendampingan Sosialisasi Promosi dan Penjualan Produk Pilus Rumput Laut UMKM Molek di Desa Labuhan Haji - Yuniar Affandy; Salmi Yuniar Bahri; Masbullah Masbullah; Adatya Bias Yumam; Agus Putra (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
In the community service activities conducted in Labuhan Haji Village, research was carried out on the Micro, Small, and Medium Enterprise (MSME) of Seaweed Pilus located in Dusun Labuaji, Labuhan Haji Village, Labuhan Haji Subdistrict, East Lombok Regency, West Nusa Tenggara. This activity aimed to develop sales improvement strategies through sales promotion assistance, with the goal of increasing product sales in the future. The community service activity was conducted using a descriptive method, accompanied by an analysis of internal and external factors, packaging, promotion, and marketing. The production process carried out by the partner remains relatively simple, both in terms of marketing and product manufacturing. The products are packaged using plastic materials and labeled with a very basic logo. During the community service activity, we, as student members of Group 5 in Labuhan Haji Village, provided direct assistance to the business. It is hoped that the activities we carried out will bring tangible benefits to the partner in developing and advancing their business.